2017
DOI: 10.1021/acs.est.7b00872
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Peroxisome Proliferator-Activated Receptor Gamma and Disruption of Progesterone Synthesis of 2-Ethylhexyl Diphenyl Phosphate in Human Placental Choriocarcinoma Cells: Comparison with Triphenyl Phosphate

Abstract: 2-Ethylhexyl diphenyl phosphate (EHDPP), an organophosphate flame retardant (OPFR), is frequently detected in human blood. In this study, the sensitive dual-luciferase reporter gene assay and molecular docking were used to investigate the activation of EHDPP to human peroxisome proliferator-activated receptor gamma (PPARG). Results show that EHDPP exhibited stronger PPARG activation (EC: 2.04 μM) than triphenyl phosphate (TPhP) (EC: 2.78 μM). EHDPP upregulated the gene expression of 3β-hydroxysteroid dehydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 34 publications
2
45
0
Order By: Relevance
“…One study in mice demonstrated that in utero exposure to triphenyl phosphate (TPhP), the parent compound of DPhP, alters fetal and maternal liver insulin growth factor signaling, which is critical to the control of fetal growth and development [ 57 , 58 ]. Additional research using a human placental cell line has also established that TPhP exposure increases both progesterone and human chorionic gonadotropin secretion via activation of the peroxisome proliferator-activated receptor gamma [ 59 ]. Changes to placental hormone production has important implications for both placental and fetal growth and development [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study in mice demonstrated that in utero exposure to triphenyl phosphate (TPhP), the parent compound of DPhP, alters fetal and maternal liver insulin growth factor signaling, which is critical to the control of fetal growth and development [ 57 , 58 ]. Additional research using a human placental cell line has also established that TPhP exposure increases both progesterone and human chorionic gonadotropin secretion via activation of the peroxisome proliferator-activated receptor gamma [ 59 ]. Changes to placental hormone production has important implications for both placental and fetal growth and development [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several biological mechanisms by which OPEs could alter metabolism have been proposed. Emerging laboratory and human evidence indicates that OPEs may interfere with sex steroid and thyroid hormones ( Farhat et al 2013 ; Kim et al 2015 ; Krivoshiev et al 2016 ; Liu et al 2012b ; Meeker and Stapleton 2010 ; Preston et al 2017 ; Schang et al 2016 ; Wang et al 2015 ; Zhang et al, 2016a ), peroxisome proliferator-activated receptors (PPARs) ( Belcher et al 2014 ; Fang et al 2015 ; Hu et al 2017 ; Kojima et al 2013 ; Pillai et al 2014 ), and induce oxidative stress ( Arukwe et al 2016 ; Chen et al 2015 ; Jin et al 2016 ; Lu et al 2017 ; Yan et al 2017 ). These biologic pathways serve well-known roles in adipose tissue development and obesity risk.…”
Section: Introductionmentioning
confidence: 99%
“…One study in mice demonstrated that in utero exposure to triphenyl phosphate (TPhP), the parent compound of DPhP, alters fetal and maternal liver insulin growth factor signaling, which is critical to the control of fetal growth and development (57,58). Additional research using a human placental cell line has also established that TPhP exposure increases both progesterone and human chorionic gonadotropin secretion via activation of the peroxisome proliferator-activated g p p p receptor gamma (59). Changes to placental hormone production has important implications for both placental and fetal growth and development (58).…”
Section: Discussionmentioning
confidence: 99%